Impact of forest fires on PAH levels in groundwater from mountain areas - Mansilha, Catarina (2014)
Wildfires, both natural and manmade, are a major environmental hazard with significant short-term and long-term effects on human health and environment. Independently of fire type and intensity, the combustion process generates huge amounts of carbon dioxide and several groups of pollutants such as dioxins, dibenzofurans and polycyclic aromatic hydrocarbons (PAHs). Due to their potential adverse effects on humans and wildlife, PAHs are registered on European and American lists of priority pollutants that must be monitored in environment 1. Several PAHs compounds can increase the incidence of cancer, and are also referred to as endocrine disruptor compounds, with the most well-known marker being benzo[a]pyrene 2,3. Regarding water quality, PAHs were firstly considered priority hazardous substances (those presenting a significant risk to or via the aquatic environment) by the Decision nº2455/2001/EC of the European Parliament and of the Council, which becomes Annex X of the Water Framework Directive (2000/60/EC). This list was then replaced by Annex II of the Directive 2008/105/EC, known as the Priority Substances Directive, subsequently reviewed by the Commission in 2012 (COM(2011) 876 final. Until now, there are still substantial knowledge gaps about the water quality impacts of forest fires concerning PAHs contamination 3. The aim of this study was to analyse groundwater samples from two granitic mountain regions located in protected areas: Serra da Estrela (Central Portugal) and Serra do Gerês (North Portugal). The sampling networks were established in order to include springs from water table aquifers in areas affected by wildfires which took place in different years in order to determine contents of 16 priority PAHs. All the selected sampling points keep flowing throughout the year (in order to avoid temporary springs supplied by interflow) and are located upstream from roads (so that PAHs originated by road traffic are not present). The contribution of wildfires to the content of PAHs in water was demonstrated, as well as the effect of the influence of the time elapsed since the last fire. The PAHs naphthalene, fluorene, anthracene, dibenzo(a,h)antracene, benzo(ghi)perylene and indene(1,2,3-cd)pyrene appear to be the major ones produced. Naphtalene, anthracene and indene(1,2,3-cd)pyrene levels were remarkably high comparing to the control water sample and still remain in water several years after the last fire event.